Root resorption of self-ligating and conventional preadjusted brackets in severe anterior crowding Class I patients: a longitudinal retrospective study - Chen, Weiting; Haq, Abdul Azeem Aminul; Zhou, Yu (BMC oral health, 2015)
To test the null hypothesis that there is no difference in the apical root resorption seen after orthodontic treatment with the conventional brackets and the self-ligating brackets. Pre-treatment and post-treatment periapical radio-graphs of 70 patients, (35 treated with the Damon3 0.022" bracket and 35 with the 0.022" 3 M bracket) were studied. The long cone paralleling technique was used for all the radio-graphs. Any image distortion between the pre-treatment and post-treatment radio-graph was calculated and compensated for by using the crown length measurements, on the assumption that the crown length remains unaltered during the treatment period. Quantitative measurements of crown and root lengths for the maxillary and the mandibular central and lateral incisors were compared. Means and standard deviations for the percentage root resorption per tooth group were calculated. A paired t-test and non paired t-test analysis was performed to determine whether there was an appliance, treatment time, or initial age effect on the amount of root resorption seen after treatment. No statistically significant difference in root resorption between the two appliance systems was found. The patient's degree of root resorption were graded as grade 1 and grade 2 in the self-ligating group which is more than the conventional group. There was no significant difference in root resorption between self-ligating brackets and conventional brackets in severe crowding incisors subjects.